Do Social Media, Tourism Destination Image and Product Destination Play a Significant Role in Influencing Tourist Decision Making? Evidence from Local Destination in North Sulawesi - Angriani Asnawi, Melan (ADPEBI, 2022)
This research aims to examine and analyse the relationship between the role of social media, tourism destination image and product destination on tourist decision making. It is happened due to such great potential tourism industry which Indonesia has, considering able to contribute in developing the Economic of Nation. However, during the Covid-19 pandemic for over the past two years (2020-2021) Indonesia tourism industry experienced such a decreasing the number visitors. Thus, it is prominent for Indonesia to attract the number of visitors to travel to Indonesia. This is a quantitative research, using primary data which obtained by questionnaire with random sampling technique then, it analysed by SPSS as a statistic tool to illustrate the correlation between each variable. Furthermore, this research peaks local destination in North Sulawesi as main object to represent one of tourism industries in Indonesia and reached 115 samples (local visitors). Furthermore, the results showed that the role of social media and product destination have positive and significant effect in influencing tourist decision making while deciding such local destination in North Sulawesi. However, the variable of tourism destination image proven insignificant effect on tourist decision making.